Habitus Musisi di Era Digital: Media Sosial sebagai Ruang Ekspresi dan Tekanan - Sang Nyoman Satria Irnanningrat; Hidayatul Nurjanah (Institut Seni Indonesia Denpasar, 2026)
Purpose: The purpose of this research is to explores the dynamics of interaction between classically or academically trained musicians and the culture of social media, using Pierre Bourdieu’s theory of habitus as the main analytical framework. The study aims to understand how the habitus of classical musicians is challenged, negotiated, and transformed within the digital environment. Method: This study applies a qualitative case study approach involving three Indonesian classical musicians: Balawan, Lianto Tjahjoputro, and Erika Soehartono. Data were collected through documentation of their activities on YouTube, Instagram, and Facebook, as well as analysis of user-generated comments. Result and Discussion: The findings indicate a tension between the disciplined and reflective habitus of classical musicians and the fast-paced, visibility-oriented logic of social media. While these musicians gain appreciation and wider exposure, they also encounter negative comments, social comparison, body shaming, and demands for continuous content production. This mismatch creates psychological pressure and, in some cases, leads to stress and digital burnout. Implication: Social media functions as an ambivalent space that offers opportunities for expression while also posing challenges to artistic integrity. Therefore, musicians need adaptive strategies to navigate digital cultural expectations without compromising their artistic values.